The Ethnographic Principle as a Phenomenon of History - Laurinavičius, Česlovas (Lietuvos istorijos studijos, 2021)
The concept of the ethnographic principle is rarely found in the literature, and there is hardly a legal qualification for it. However, historical material (in cases of the Lithuanian, Czech, Bulgarian and Polish peoples) indicates that the ethnographic principle is a significant political and geopolitical phenomenon. This phenomen is especialy characteristic of the development of the peoples of the region of Central and Eastern Europe. First, the ethnographic principle was closely related to the national principle, although it did not coincide with it. The concept of the ethnographic principle points to the special anatomy of nation states, where the basis is ethnic / linguistic culture. Secondly, the advancement of culture to the fore indicated the recognition of its significance, which had not happened before. Consequently, it was a question of freeing this culture from the restrictions imposed on it and even compensating for the damage caused to it. Thirdly, the culture, raised to the state level, needed appropriate guarantees for the future. The article reveals the tendency of great states at the level of their policies and propaganda to act according to the ethnographic principle, thereby encouraging the formation of national states. However, when the latter became a fact, another tendency arose: the Western world began to apply the criteria of a liberal civil society to new states (according to the principle of jus civis romanus sum). This was too hard for the new states. In this context, the alternative was the Soviet ethno-federalist protectorate, which, although under the conditions of a repressive system, actually continued to implement the projections of the ethnographic principle. A fixed paradox: the ethnographic principle, which originated in the West as a variant of democratization, gained strength thanks to Russia, while the West remained, as it were, in aristocratic opposition to this course. The ethnographic principle has not yet acquired a clearer legal legitimacy. But as a historical category, it can serve as a study of the history of Modern times, and especially the Soviet period.